Decision-making under stress: A psychological and neurobiological integrative model - Sarmiento, Luis Felipe (2024)
Understanding the impact of stress on cognitive processes, particularly decision-making, is crucial as it underpins behaviors essential for survival. However, research in this domain has yielded disparate results, with inconsistencies evident across stress-induction paradigms and drug administration protocols designed to investigate specific stress pathways or neuromodulators. Building upon empirical studies, this research identifies a multifaceted matrix of variables contributing to the divergent findings. This matrix encompasses factors such as the temporal proximity between stressors and decision tasks, the nature of stressors and decision contexts, individual characteristics including psychobiological profiles and affective states at the time of decision-making and even cultural influences. In response to these complexities, we propose a comprehensive model that integrates these relevant factors and their intricate interplay to elucidate the mechanisms governing decision-making during stressful events. By synthesizing these insights, our model not only refines existing paradigms but also provides a framework for future study designs, offering avenues for theoretical advancements and translational developments in the field of stress´s impact on cognitive functions. This research contributes to a deeper understanding of the nuanced relationship between stress and decision-making, ultimately advancing our knowledge of cognitive processes under challenging conditions.